Emotional bonding with Artificial Intelligence in loneliness: A neuropsychological perspective from a case study (Research, Society and Development, 2025)
This clinical case study aims to analyze, from a neuropsychological perspective, the repercussions of intensive use of artificial intelligence (AI) as an emotional companion on cognitive and affective functions, as well as to reflect on its clinical and ethical implications. A qualitative, exploratory case study design was adopted. The research was based on the hypothesis that recurrent use of artificial agents may function as a substitute for human bonding, negatively impacting social cognition and reinforcing patterns of affective avoidance. Grounded in an integrative literature review and in the neuropsychological assessment of the participant, the study integrated data obtained through clinical interviews, psychometric tests, projective techniques, and the Loneliness and AI Attachment Scale (SVIA), developed specifically for this investigation. The results indicated preservation of overall intellectual functioning, with specific vulnerabilities in executive functions, particularly cognitive flexibility and social cognition. High inhibitory control, low affective spontaneity, and a strong preference for artificial bonds were also observed, suggesting a defensive pattern compatible with schizoid traits. These findings reinforce warnings in the literature regarding the emotional and cognitive impacts of digitally mediated loneliness. From a clinical and ethical standpoint, the study highlights the importance of interventions that take into account the effects of technology on attachment processes. Psychotherapy focused on social cognition, strengthening relational experiences, and the progressive integration of affect is recommended. This research contributes to expanding the debate on the use of AI in affective contexts, proposing a critical reflection on its risks and possibilities.